Reading other peoples' texts social identity and the reception of authoritative traditions - Brown, Ken 1982-; Joseph, Alison L.; Breed, Brennan W. (London Bloomsbury Publishing Plc, 2020)
Cover -- Titel -- Copyright -- Contents -- List of Contributors -- Preface -- Abbreviations -- Social Identity and Scriptural Interpretation: An Introduction Ken Brown and Brennan Breed -- Boundaries and Bridges: Journeys of a Postcolonial Feminist in Biblical Studies Musa W. Dube -- Reading without History Michael L. Satlow -- What Happens to Precursor Texts in Their Successors? Robert L. Brawley -- Redaction as Reception: Genesis 34 as Case Study Alison L. Joseph -- Between Our Ancestors and the Other: Negotiating Identity in the Early Reception of the Water from the Rock Ken Brown -- Abrahamic Identity in Paul and Liber Antiquitatum Biblicarum Kyle B. Wells -- Heracles between Slavery and Freedom: Subversive Textual Appropriation in Philo of Alexandria Courtney J. P. Friesen -- Perspectives on a Pluriform Classic C. L. Seow -- Iconoclastic Readings: Othering in Isaiah 44 and in Its Reception in Biblical Scholarship Sonja Ammann -- Biblical Scholars' Ethos of Respect: Original Meanings, Original Texts, and Reception History of Ecclesiastes Brennan Breed -- Bibliography -- Index of References -- Index of Authors -- Index of Subjects.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Aufsatzsammlung